Contact lens associated microbial keratitis: practical considerations for the optometrist - Zimmerman AB; Nixon AD; Rueff EM (Clinical Optometry, 2016)
Aaron B Zimmerman, Alex D Nixon, Erin M Rueff College of Optometry, The Ohio State University, Columbus, OH, USAAbstract: Microbial keratitis (MK) is a corneal condition that encompasses several different pathogens and etiologies. While contact lens associated MK is most often associated with bacterial infections, other pathogens (fungi, Acanthamoeba species, etc) may be responsible. This review summarizes the risk factors, microbiology, diagnostic characteristics, and treatment options for all forms of contact lens-related MK.Keywords: corneal ulcer, fungal keratitis, bacterial keratitis, Acanthamoeba, Fusarium, Pseudomonas